Variability in stover quality traits in commercial hybrids of pearl millet (Pennisetum glaucum (L.) R. Br.) and grain-stover trait relationships - Blümmel, Michael; Khan, A.A.; Vadez, Vincent; Hash, C.T.; Rai, Kedar N. (2010)
Pearl millet stover is an important cattle feed particularly in arid areas and nutritional quality traits of the stover become more and more important. Eight commercial and two experimental hybrids of pearl millet were evaluated for stover fodder quality traits and their potential trade-off with stover and grain yield. The stover quality traits analyzed were nitrogen, in vitro digestibility and metabolisable energy content. Highly significant (P<0.01) variations were observed for grain yields (2860 to 4220 kg/ha), stover yields (range 3760 to 4930 kg/ha), stover nitrogen (0.62 to 1.10%), stover in vitro digestibility (37.6 to 46.7%) and stover metabolisable energy (5.26 to 6.88 MJ/kg). Stover nitrogen content was negatively associated with grain and stover yield but no such trade-offs were observed between stover in vitro digestibility and metabolisable energy contents on one hand and grain and stover yield on the other. Hybrid GK 1044 had the lowest stover nitrogen content (0.62%) and highest stover digestibility (46.7%) and metabolisable energy (6.88 MJ/kg), while MLBH 267 with the highest stover nitrogen (1.10%) and the lowest stover digestibility (37.6%) and metabolisable energy (5.26 MJ/kg). These two contrasting hybrids were re-planted on large plots in the second year and their stover tested in vivo with sheep as sole feed. Digestible organic matter intake was significantly higher in GK 1044 than in MLBH 267 (13.5 versus 12.5 gram per kg live weight) and nitrogen balance tended (P<0.10) to be more favourable in GK 1044 than in MLBH 267 (−0.008 versus -0.10 gram per kg live weight. These results show that among commercial high-yielding pearl millet hybrids, some can be found with high grain and stover yield, high stover digestibility and metabolisable energy. The observations from the feeding trial suggest that stover in vitro digestibility and metabolisable energy are more important than stover nitrogen content in determining stover quality.